1991
DOI: 10.1210/jcem-72-5-1014
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Insulin-Like Growth Factor-Binding Protein-1 Synthesis and Secretion by Progestin and Relaxin in Long Term Cultures of Human Endometrial Stromal Cells*

Abstract: The decidualized endometrium during the first trimester of pregnancy synthesizes and secretes a 32-kDa insulin-like growth factor-binding protein (termed hIGFBP-1) at high levels. IGFBP-1 is the major soluble protein product of this tissue and is principally localized to the differentiated endometrial stromal cell, the decidual cell. In the present study long term culture of stromal cells from the nonpregnant endometrium have been employed to elucidate the hormonal requirements for IGFBP-1 production. Immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(72 citation statements)
references
References 49 publications
5
65
1
Order By: Relevance
“…Circulating relaxin (RLX) levels rise during the luteal phase (Bond et al 2004, Hayes 2004 and its detection in the endometrium during natural cycles coincide with the period of endometrial receptivity (Yki-Jarvinen et al 1985) suggesting a role in the early events of embryo implantation. Several studies show that RLX exerts a wide range of effects on the human endometrium mediating differentiation, vascularization and immunomodulation in this tissue (Goldsmith & Weiss 2009 Bell et al 1991), glycodelin (Tseng et al 1999) and vascular endothelial growth factor (VEGF; Unemori et al 1999, Palejwala et al 2002. The results obtained in the present study cannot distinguish between genes that are regulated by P 4 and those whose transcript levels are regulated by the presence of estrogens, relaxin or other factors.…”
Section: Endometrial Gene Expression Profile After Mifepristonecontrasting
confidence: 70%
“…Circulating relaxin (RLX) levels rise during the luteal phase (Bond et al 2004, Hayes 2004 and its detection in the endometrium during natural cycles coincide with the period of endometrial receptivity (Yki-Jarvinen et al 1985) suggesting a role in the early events of embryo implantation. Several studies show that RLX exerts a wide range of effects on the human endometrium mediating differentiation, vascularization and immunomodulation in this tissue (Goldsmith & Weiss 2009 Bell et al 1991), glycodelin (Tseng et al 1999) and vascular endothelial growth factor (VEGF; Unemori et al 1999, Palejwala et al 2002. The results obtained in the present study cannot distinguish between genes that are regulated by P 4 and those whose transcript levels are regulated by the presence of estrogens, relaxin or other factors.…”
Section: Endometrial Gene Expression Profile After Mifepristonecontrasting
confidence: 70%
“…In contrast, there is no difference in circulating IGFBP-1 levels between IUCD (without progestin) users and non-IUCD users (Seleem et al 1996). Studies using cell cultures have also shown that progesterone (medroxyprogesterone acetate) stimulates IGFBP-1 secretion in cultured endometrial stromal cells (Bell et al 1991). These findings further confirm that synthesis of endometrial IGFBP-1 is progesterone dependent ( Julkunen et al 1988, Rutanen & Pekonen 1991).…”
Section: Regulation Of Proliferation and Differentiation In The Endommentioning
confidence: 74%
“…Insulin-like growth factor binding protein-1 (IGFBP-1) is highly expressed during decidualisation and this expression is progesterone-dependent, as is Hoxa10 (Bell et al, 1991). HOXA10 activates the IGFBP-1 promoter in various types of endometrial cells (Gao et al, 2002) in cooperation with FKHR, a member of the FOXO subfamily of forkhead (fkh) transcription factors (Kim et al, 2003).…”
Section: Mammalian Gene Targets Of Hox Proteins T Svingen and Kf Tonimentioning
confidence: 99%